Materialism and Compulsive Buying – Conceptual Underpinning - Manchanda, Rimple (Journal of Contemporary Research in Management (JCRM), 2016)
In the modern life style, compulsive buying is found to be very common and consequently the studies on antecedents of compulsive buying have increased in recent years. Materialism and compulsive buying are the two important factors which influence the buying decisions of consumers and also distinguish them from each other. India is one of the oldest civilizations and has profound values on money, materialism and consumption. However, during last two decades the wave of globalization has brought India much closer to rest of world both culturally and economically. Advancement of shopping malls, retail brand, exclusive stores and use of media with best of its creativity and reach to persuade consumers has made a positive change in the consumer response to market stimuli. In this perspective, the present study aims at exploring the existence of such behaviours in our society.